University partnerships for international development - Blessinger, Patrick; Cozza, Barbara (Bingley : Emerald Group Publishing Limited, 2016)
This volume examines the diverse ways universities and colleges around the world are partnering and collaborating with other institutions to fulfill their missions and visions. University partnerships not only include collaborations between universities but also include university-school (basic education) collaborative partnerships to improve local school systems. The increasing pressures to remove access and participation barriers, and the increasing pressures to mitigate practices that restrict the free flow of education across borders have created a growing global space for educational services of all types. As a result, traditional institutional boundaries have expanded to better respond to increasing pressures placed on them by the growing demand for higher education services. The boundaries between educational institutions and other entities such as government, business, and non-profit organizations have become more fluid and this has resulted in increased involvement by institutions, faculty, and students in activities outside the traditional boundaries of the classroom. This edited volume will specifically explore university partnerships for international development.
Prelims -- Part I: concepts and principles -- Part II: successful practices.
Includes bibliographical references.
Print version record
Keywords: Education -- Higher; Universities; Education, Higher -- International cooperation; Academic-industrial collaboration; College-school cooperation